LITERASI POLITIK MASYARAKAT DI ERA DIGITAL MENJELANGPEMILU 2024 MENGGUNAKAN METODE NETNOGRAFI MEME POLITIK PADA AKUN INSTAGRAM @poliklitik - Isma Naziatul Wardah, (2022)
The development of information media has undergone very rapid changes. The development of the internet has made it easier for people to access all kinds of information in digital media. The increasingly diverse news delivery has made memes become quite famous media after the existence of a prominent meme during the 2016 American general election, namely #ZodiacTed. Memes are the subject of information delivery, satire, satire and sara. The @poliklitik account is one of the digital media that makes memes into information media that contain social, cultural and political for the public on the Instagram platform. The sleek delivery, prominent visuals and lightness make it an attraction in itself. In this study, how the understanding of the information conveyed on the @poliklitik account is related to memes containing political news, whether it is conveyed well and the public understands the content of the news that is prepared. So that the purpose of the research can be conveyed as a political tool in conveying messages related to the 2024 elections and knowing the visual culture on Instagram @poliklitik. Using the netnography method, the author explains the understanding of people's political literacy related to political memes that are posted on @poliklitik accounts with Insider qualifications from the three posts studied by speakers related to the upcoming 2024 elections and sees their responses and behaviors from behavioral beasic using social reality construction theory. From the results of this study, it can be seen whether the delivery of information media in the form of memes can be understood by the public and influence people's thinking related to political memes that discuss the upcoming 2024 elections. Keywords: the development of information media, political memes, literacy, netnographic methods, @poliklitik accounts, behavioral, social reality theory